The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae - Short, Megan; Vahtera, Varpu; Wesener, Thomas; Golovatch, Sergei I. (Zootaxa, 2020)
The Polyxenidae in the fauna of the Crimeo-Caucasian region is represented by four species: Polyxenus lagurus (Linnaeus, 1758) (= P. lagurus caucasicus Lignau, 1924, syn. n.), Propolyxenus argentifer (Verhoeff, 1921) comb. n. (= P. trivittatus Verhoeff, 1941, = P. sokolowi Lignau, 1924, both syn. n.), a new species, Polyxenus lankaranensis sp. n., and an undescribed Polyxenus sp. The distributions of all these species in the region concerned are mapped, based on old and new records. A molecular phylogeny based on COI sequences is used to study the relationship within and among the genera Polyxenus and Propolyxenus from Western Europe to the southern Caucasus. The results highlight the presence of a number of undescribed species of Polyxenus across this region.